METHODOLOGY OF TEACHING THE RUSSIAN LANGUAGE IN UZBEK GROUPS - Gulistan Kosbergenovna Musayeva (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the teaching of the Russian language in secondary schools in Uzbekistan. The main attention is focused on the most modern methods of teaching the Russian language in Uzbek-teaching schools.